Environmental challenges in hemodialysis: Exploring the road to sustainability - Marta Arias-Guillén; Rodrigo Martínez Cadenas; Miquel Gómez; Natalia Martín Vaquero; Gerard Pereda; Julia Audije-Gil; Jesús Portillo; Marta Quintela; Itziar Castaño; Antonio Luque; Francesc Maduell; Alberto Ortiz; et al. (Nefrología (English Edition))
Hemodialysis (HD) is a treatment with a significant environmental impact. One dialysis cycle is equivalent to the daily consumption of 3.5–4 people, and the average annual electricity consumption of a center is equivalent to that of approximately 2.5–3 households (9 kWh/day per household). The carbon footprint (kg CO2 equivalent) measures direct and indirect greenhouse gas emissions and is influenced by the production of the various materials used, their transport, patients, and healthcare personnel. In this context, it is necessary to understand the real impact of each center on the environment and act sustainably. The aim of this review is to analyze the environmental footprint generated by dialysis, rethink processes, and propose management strategies to provide tools applicable to any unit to reduce the negative impact of this activity. Each center must measure and monitor indicators, set its own standards, design improvement plans, and carry out annual monitoring in a multidisciplinary manner. Resumen: La hemodiálisis (HD) es un tratamiento con gran impacto en el medio ambiente. Un ciclo de diálisis equivale al consumo diario 3,5−4 personas y el consumo anual medio de electricidad de un centro se equipara al de aproximadamente 2,5 a 3 hogares (9 kWh/día por hogar). La huella de carbono (kg CO2 equivalente) es la medida de las emisiones directas e indirectas de gases de efecto invernadero y está influida por la producción de los distintos materiales utilizados y el transporte de estos, de los pacientes y el personal sanitario. En este contexto se hace necesario conocer el impacto real de cada centro en el mediomabiente y actuar de una manera sostenible. El objetivo de esta revisión es analizar la huella medioambiental que genera la diálisis, repensar los procesos y plantear estrategias de gestión con el fin de aportar herramientas aplicables a cualquier unidad para reducir el impacto negativo de esta actividad. Cada centro debe medir y hacer seguimiento de indicadores, fijar su estándar, diseñar planes de mejora y realizar seguimiento anual de manera multidiciplinar.